Neural circuit research using molecular barcode technology - Yasuhiro Go (Neuroscience Research)
In neuroscience research, the primary goal is to understand the complex morphological and anatomical structures of the brain and their physiological and behavioral functional relationships or to understand the causality of diseases that manifest as dysfunction of the brain, and various technologies have been developed to achieve this goal. These include imaging techniques such as magnetic resonance imaging (MRI), functional magnetic resonance imaging (fMRI), and positron emission tomography (PET), which noninvasively visualize brain structure and activity; electrophysiological techniques that measure intracellular potentials and currents and analyze cell electrical properties to understand brain activity; techniques to explore how gene expression affects brain function; genetic methods such as gene knockout/knock-in to study how brain cells function; and computational neuroscience methods such as mathematical modeling and simulation to understand the principles of how brain networks operate. Among these, recent advances, particularly the development of 'single-cell omics analysis,' have led to a paradigm shift in neuroscience research. This technique allows the comprehensive study of the unique genetic and molecular characteristics of individual brain cells at the single-cell level. In this paper, I review the application of single-cell omics analysis, which has advanced dramatically in recent years, to various neuroscience problems, mainly how it contributes to the structure and function of neural circuits, a modality unique to the cranial nervous system.